Drug resistance of bladder cancer cells through activation of ABCG2 by FOXM1 - Roh, Yun-Gil; Mun, Mi-Hye; Jeong, Mi-So; Kim, Won-Tae; Lee, Se-Ra; Chung, Jin-Woong; Kim, Seung Il; Kim, Tae Nam; Nam, Jong Kil; Leem, Sun-Hee (BMB reports, 2018)
Recurrence is a serious problem in patients with bladder cancer. The hypothesis for recurrence was that the proliferation of drug-resistant cells was reported, and this study focused on drug resistance due to drug efflux. Previous studies have identified FOXM1 as the key gene for recurrence. We found that FOXM1 inhibition decreased drug efflux activity and increased sensitivity to Doxorubicin. Therefore, we examined whether the expression of ABC transporter gene related to drug efflux is regulated by FOXM1. As a result, ABCG2, one of the genes involved in drug efflux, has been identified as a new target for FOXM1. We also demonstrated direct transcriptional regulation of ABCG2 by FOXM1 using ChIP assay. Consequently, in the presence of the drug, FOXM1 is proposed to directly activate ABCG2 to increase the drug efflux activation and drug resistance, thereby involving chemoresistance of bladder cancer cells. Therefore, we suggest that FOXM1 and ABCG2 may be useful targets and important parameters in the treatment of bladder cancer. [BMB Reports 2018; 51(2): 98-103].